Study of doubly fed induction generator by using wound rotor induction motor in wind turbine - Nur Atteya Azmi (School of Electrical System Engineering, University Malaysia Perlis, 2011)
In 1990s, wind power turbines were characterized by a fixed speed operation. Basically, they consisted of the coupling of a wind turbine, a gearbox and an induction machine directly connected to the grid. Wind energy has become one of the most important and promising sources of renewable energy that demands additional transmission capacity and better means of maintaining system reliability. In order to meet the power needs, taking into account economical and environmental factors, wind energy conversion is gradually gaining interest as a suitable source of renewable energy. The electromagnetic conversion is usually achieved by induction machines or synchronous and permanent magnet generators. In order to enable variable speed operations with a lower rated power converter, Doubly-Fed Induction Generator (DFIG) is suitable and can be used. The stator is directly connected to the grid and the rotor is fed to magnetize the machine. These wind energy conversion systems are connected to the grid through Voltage Sources Converter (VSC) to make variable speed operation possible. The studied system here is a variable speed wind generation system based on DFIG. This project concentrates on the comparison between the used of DFIG and other generating systems that applied in wind power generating systems, such as Permanent Magnet Synchronous Generator (PMSG). There are many advantages of DFIG compared to the other two generators in many facets. However, all kinds of generating have their own merits and demerits of their features itself. The PSCAD software is used for the simulations.